Self-control, academic anxiety, and mobile phone addiction: the moderating role of being an only child - De Su; De Su; Jiahao Zhang; Yuanyuan Ma; Ze Geng (Frontiers in Psychology)
BackgroundThe prevalence of mobile phone addiction among adolescents is a growing concern with significant implications for psychological well-being and academic performance. The mediating role of academic anxiety (AA) in the relationship between self-control (SC) and mobile phone addiction (MPA) among middle school students deserves thorough investigation, particularly considering the significant moderating effect of Being an only child on these relationships.MethodsA cross-sectional survey of 2,489 middle school students (1,257 girls and 1,232 boys) assessed SC, AA, and MPA. SC was measured using the Self-Control Scale, AA with the Academic Anxiety Scale (AAS), and MPA with the Mobile Phone Addiction Index (MPAI). Structural equation modeling analyzed the mediating and moderating effects.ResultsSelf-control significantly negatively predicted AA (β = −0.464, p < 0.001) and MPA (β = −0.563, p < 0.001). AA was identified as a significant mediator that positively predicted MPA (β = 0.173, p < 0.001) and mediated the relationship between SC and MPA (β = 0.081, 95%CI = [−0.10, −0.06]). The moderating effect of being an only child on the relationship between AA and MPA (β = −0.13, p < 0.001) was significant.ConclusionThe empirical evidence substantiates the mediating role of AA in the relationship between SC and MPA, while simultaneously demonstrating that only children exhibit heightened susceptibility to MPA with increasing AA levels. Such observations significantly advance our understanding of the influence of family dynamics on MPA manifestation among adolescents.